MODEL LESSON STUDY UNTUK PENINGKATAN PRESTASI MAHASISWA DALAM PROSES PEMBELAJARAN PADA PERKULIAHAN KINESIOLOGI - Sigit Nugroho (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: Lesson Study Model to Improve Students’ Achievement in the Instructions Process of Kinesiology Classes. This study aims to improve the quality of students’ kinesiology achievement in the Faculty of Sports Sciences, the Yogyakarta State University. The participants were 43 students attending Sports Science Courses. This study was an action research study consisting of two cycles. The data were analyzed using the descriptive technique, consisting of (1) description, (2) validation, and (3) interpretation. The first cycle showed that the quality of learning was still low. In the second cycle, there was an improvement after the CD with audio visual media was played. The learning process through kinesiology lesson study with a sports analysis increased students' understanding. Based on the results of the reflection and discussion on the action, learning through lesson study by preparing materials using audio visual media can improve the quality of kinesiology learning. Keywords: lesson study, kinesiology, quality of learning